Back pay legislation: hearing ... Eighty-ninth Congress, Second Session, on H.R. 1647, February 17, 1966. - United States. Congress. Senate. Committee on Post Office and Civil Service. Subcommittee on Civil Service (Washington, U.S. Govt. Print. Off., 1966)
Considers H.R. 1647, to provide for pay and benefits for wrongfully fired Federal employees who are reinstated by court order.
Jennings Randolph, subcommittee chairman.
Mode of access: Internet.
Keywords: Employees -- Reinstatement -- United States; United States -- Officials and employees -- Reinstatement -- Law and legislation -- Salaries, etc